2012
DOI: 10.1002/chem.201202085
|View full text |Cite
|
Sign up to set email alerts
|

Development of Zn–ProPhenol‐Catalyzed Asymmetric Alkyne Addition: Synthesis of Chiral Propargylic Alcohols

Abstract: The development of a general and practical zinc-catalyzed enantioselective alkyne addition methodology is reported. Commercially available ProPhenol ligand (1) has facilitated the addition of a wide range of zinc alkynylides to aryl, aliphatic and α,β-unsaturated aldehydes in high yield and enantioselectivity. New insights into the mechanism of this reaction have resulted in a significant reduction in reagent stoichiometry, enabling the use of precious alkynes and avoiding the use of excess dimethylzinc. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 141 publications
1
22
0
4
Order By: Relevance
“…[38] Nonetheless, a wide range of aromatic, a,bunsaturated, and aliphatic aldehydes 7 reacted with aryl, alkyl and silyl acetylenes in high yield and ee, as shown in Scheme 18. [39] In particular, trimethylsilyl acetylene and methyl propiolate gave excellent results (up to 97 % ee). Similar results were also obtained for product 66 f using only 1.5 equivalents of zinc reagents.…”
Section: Asymmetric Alkyne Additionmentioning
confidence: 98%
See 1 more Smart Citation
“…[38] Nonetheless, a wide range of aromatic, a,bunsaturated, and aliphatic aldehydes 7 reacted with aryl, alkyl and silyl acetylenes in high yield and ee, as shown in Scheme 18. [39] In particular, trimethylsilyl acetylene and methyl propiolate gave excellent results (up to 97 % ee). Similar results were also obtained for product 66 f using only 1.5 equivalents of zinc reagents.…”
Section: Asymmetric Alkyne Additionmentioning
confidence: 98%
“…During reaction optimization, it was revealed that the alkynylation process generally required 2–3 equiv of dimethylzinc for high conversion and ee . Nonetheless, a wide range of aromatic, α,β‐unsaturated, and aliphatic aldehydes 7 reacted with aryl, alkyl and silyl acetylenes in high yield and ee , as shown in Scheme . In particular, trimethylsilyl acetylene and methyl propiolate gave excellent results (up to 97 % ee ).…”
Section: Catalytic Asymmetric Addition To Carbonylsmentioning
confidence: 99%
“…Während der Reaktionsoptimierung wurde erkannt, dass der Alkinylierungsprozess generell 2–3 Äquivalente Dimethylzink für hohe Umsätze und ee ‐Werte erforderte . Dessen ungeachtet ließ sich ein breites Spektrum an aromatischen, α,β‐ungesättigten und aliphatischen Aldehyden 7 mit Aryl‐, Alkyl‐ und Silylacetylenen mit hohen Ausbeuten und ee ‐Werten umsetzen, wie dies in Schema gezeigt ist . Insbesondere Trimethylsilylacetylen und Methylpropiolat lieferten ausgezeichnete Ergebnisse (bis zu 97 % ee ).…”
Section: Katalytische Asymmetrische Addition An Carbonyleunclassified
“…[38] Dessen ungeachtet ließ sich ein breites Spektrum an aromatischen, a,b-ungesättigten und aliphatischen Aldehyden 7 mit Aryl-, Alkyl-und Silylacetylenen mit hohen Ausbeuten und ee-Werten umsetzen, wie dies in Schema 18 gezeigt ist. [39] Insbesondere Trimethylsilylacetylen und Methylpropiolat lieferten ausgezeichnete Ergebnisse (bis zu 97 % ee). ¾hnliche Ergebnisse wurden auch für das Produkt 66 f bei Einsatz von nur 1.5 ¾quivalenten Zinkreagenz erhalten.…”
Section: Asymmetrische Alkin-additionunclassified
“…After filtration, the solvent was removed in a rotary evaporator, to give 55% of a yellow oil. [31]. Isano oil (0.15 gr) and Adam's catalyst (5 mol%) were mixed in ethyl acetate (50 mL).…”
Section: Extraction Of Oilmentioning
confidence: 99%